Comparative morbidity and mortality from cervical or thoracic esophageal anastomoses. Issue 7 (21st September 2013) - Shah, Dhruvil R.; Martinez, Steve R.; Canter, Robert J.; Yang, Anthony D.; Bold, Richard J.; Khatri, Vijay P.
<x xml:space="preserve">Abstract</x> Background In the modern era of esophagectomy, we hypothesized that perioperative morbidity and mortality from cervical or thoracic sites of anastomoses would not be different. Methods We used the American College of Surgeons National Surgical Quality Improvement Program database to identify patients who underwent esophagectomy for lower esophageal or gastroesophageal (GE) junction malignancies from 2005 to 2010. Patients were categorized as having either a cervical or thoracic anastomosis based on CPT codes. Results There were 601 (66%) cervical and 308 (34%) thoracic anastomoses. Cervical anastomoses were associated with greater than 2 units of blood transfusion in a higher proportion of patients (10% vs. 3%, P = 0.001), and higher superficial surgical site infections (13% vs. 7%, P = 0.003). There were no difference in rates of organ/space infections (6% vs. 7%, P = 0.70), overall morbidity (38% vs. 39%, P = 0.84), or mortality (3% vs. 4%, P = 0.34). Median length of stay was similar (11.5 days cervical vs. 11 days thoracic, P = 0.89), even among patients with organ/space infections (18 days cervical vs. 21 days thoracic, P = 0.49). On multivariate analysis thoracic anastomosis was not a significant predictor of increased overall morbidity (OR 1.13: 95%CI 0.83–1.54). Conclusion After esophagectomy, the site of anastomosis does not predict an increased risk of perioperative morbidity or mortality. J. Surg. Oncol. 2013; 108:472–476. © 2013 Wiley Periodicals, Inc.